AB0439 T Cell CD80/Cd86 Co-Stimulatory Blockade Does not Suppress CD8 (+) Subpopulation in the Course of 48-Week Treatment of Patients with Rheumatoid Arthritis. (10th June 2014) - Murakami, M.; Ito, M.N.; Sekiguchi, M.; Matsui, K.; Kitano, M.; Imura, Y.; Ohmura, K.; Fujii, T.; Kuroiwa, T.; Maeda, K.; Morita, S.; Kawahito, Y.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a common immflamatory autoimmune disease characterized by persistent synovitis and progressive destruction of cartilage and bone in multiple joints. Biological agents have shown enhanced efficacy in patients with RA. Beside their beneficial effects, one of the main safety concerns is an increased risk of infection. CD8 (+) T cells play important roles in the immune surveillance system. Abatacept (ABA) is a T cell inhibitor biologic agent, consisting of extracellular domains from cytotoxic T-lymphocyte antigen-4 and the Fc portion of human immunoglobulin G1 (CTLA-4-Ig) which competes with CD28 on T cells for CD80/86 binding. The post marketing surveillance of ABA revealed that the serious infections were less frequent compared with the treatment using other biologic agents (ACR 2013). CD8 (+) T cells could be influenced by ABA through CD80/CD86 co-stimulatory blockade although CD28 expression on CD8 (+) T cells is lower than that on CD4 (+) T cells. Objectives: This study aims to clarify how 48-week ABA treatment affects CD8 (+) T cell subsets. Methods: Peripheral blood mononucleated cells (PBMCs) were obtained from 30 patients enrolled in abatacept research outcome as a first-line biological agent in the real world (ABROAD study) at baseline, 24 and 48 weeks of ABA treatment. Fifty-three healthy individuals (HIs) were also enrolled as controls. Surface phenotypes and activation markers of T cells were analyzed with flow cytometory. Results: DAS28-CRP and SDAI were significantly reduced at 24 and 48 weeks compared with those at baseline. The proportion of CD25 (+) in CD4 (+) T cells decreased at 24 and 48 weeks compared with that at baseline (13.9±5.4% at baseline; 6.6±5.8% at 24 weeks, p<0.0001 ; 6.1±3.1% at 48 weeks, p<0.0001 ). On the other hand, no significant reduction in the proportion of CD8 (+) T cells (19.3±11.0% at baseline, 19.0±7.9% at 24 weeks and 20.4±9.1% at 48 weeks), as well as in the proportion of CD25(+) cells in CD8 (+) T cells (3.26±2.7% at baseline, 3.4±2.5% at 24 weeks and 3.0±1.9% at 48 weeks) was observed. Conclusions: 48-week T cell co-stimulation blockade does not alter the activation status of CD8 (+) T cells while it suppresses that of CD4 (+) T cells as well as disease activities. Disclosure of Interest: M. Murakami Speakers bureau: Bristol-Myers Squibb Japan, M. Ito: None declared, M. Sekiguchi Grant/research support: Bristol-Myers Squibb Japan, Speakers bureau: Bristol-Myers Squibb Japan, K. Matsui Grant/research support: Bristol-Myers Squibb Japan, M. Kitano Grant/research support: Bristol-Myers Squibb Japan, Y. Imura Grant/research support: Bristol-Myers Squibb Japan, K. Ohmura Grant/research support: Bristol-Myers Squibb Japan, T. Fujii Grant/research support: Bristol-Myers Squibb Japan, T. Kuroiwa: None declared, K. Maeda: None declared, S. Morita: None declared, Y. Kawahito Grant/research support: Bristol-Myers Squibb Japan, T. Mimori Grant/research support: Bristol-Myers Squibb Japan, H. Sano Grant/research support: Bristol-Myers Squibb Japan, N. Nishimoto Grant/research support: Bristol-Myers Squibb Japan DOI: 10.1136/annrheumdis-2014-eular.4014